Otoritas Mufti Kerajaan Kubu: Subyektifitas, Kontestasi, dan Produksi Makna al-Qur’an - Udi Yuliarto (IAIN Bengkulu, 2023)
This paper discusses questioning the meanings based on the Quran. The main problem is how the meaning is produced in the contemporary context while still paying attention to the text of the Koran which came down almost 14 centuries ago. In this context, the researcher then uses the sociology of knowledge approach in analyzing while to ensure the research object is analyzed using religious anthropology. The result is that there are three main points of discussion in this discussion, namely; (1) Reading Ismail Mundu's Interpretation in the Identity of the Kubu Community (2) Visualization and Production of the Meaning of the Quran; An Attempt to Establish Meaning in Dialectical Space Between Mufti and Social Dimensions, (3) Subjectivity and Contestation of Meaning in Social Spatial Identity Ismail Mundu. That the meaning of the Koran is formed by social dimensions. With the conclusion that reading Ismail Mundu's interpretation in his society shows how the conditions of reality he faces. While the contestation of meaning between fiqh thinking and royal power which has the genealogy of Alawiyyin places its subjective role which is dominated by Sufistic-traditional ideas that it has acquired in social dialectical spaces.